CHAGASIC MENINGOENCEPHALITIS IN AN HIV INFECTED PATIENT WITH MODERATE IMMUNOSUPPRESSION: PROLONGED SURVIVAL AND CHALLENGES IN THE HAART ERA - BUCCHERI, Renata; KASSAB, Maria José; FREITAS, Vera Lucia Teixeira de; SILVA, Sheila Cristina Vicente da; BEZERRA, Rita C.; KHOURY, Zarifa; SHIKANAI-YASUDA, Maria Aparecida; VIDAL, José E. (Revista do Instituto de Medicina Tropical de São Paulo, 2015)
The reactivation of Chagas disease in HIV infected patients presents high mortality and morbidity. We present the case of a female patient with confirmed Chagasic meningoencephalitis as AIDS-defining illness. Interestingly, her TCD4+ lymphocyte cell count was 318 cells/mm3. After two months of induction therapy, one year of maintenance with benznidazol, and early introduction of highly active antiretroviral therapy (HAART), the patient had good clinical, parasitological and radiological evolution. We used a qualitative polymerase chain reaction for the monitoring of T. cruzi parasitemia during and after the treatment. We emphasize the potential value of molecular techniques along with clinical and radiological parameters in the follow-up of patients with Chagas disease and HIV infection. Early introduction of HAART, prolonged induction and maintenance of antiparasitic therapy, and its discontinuation are feasible, in the current management of reactivation of Chagas disease.